The influence of hydrogenation on superconducting properties of MgB2: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Zaleski, A. J.; Iwasieczko, W.; Kaczorowski, D.; Drulis, H.; Tkacz, M.; Klamut, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
In the paper we present the results of the ac susceptibility measurements of two newly discovered superconducting diboride - MgB2.